Constatative study on overweight and obesity in class iv students in suceava - Cojocaru Daniela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
Overweight and obesity have recently become public health problems, in a continuous increase, if we look mainly at the figures in the studies regarding children. More and more people of all ages, especially children, they have weight problems and are obese, having a very fast growth. Statistics from the Ministry of Health show that 40% of children are overweight, in the last 10 years their number has increased by 18%, and in terms of the number of obese children, it has doubled in the last 7 years.